Empirical Bayes Before–After Study on Safety Effect of Narrow Pavement Widening Projects in Texas. Issue 1 (January 2015) - Wu, Hui; Han, Zhe; Murphy, Michael R.; Zhang, Zhanmin
Texas has approximately 40, 000 lane miles (64, 000 lane kilometers) of two-lane farm-to-market (FM) and ranch-to-market (RM) roads with total paved widths of 18 to 22 ft (5.5 to 6.7 m), most of which are in rural areas. Narrow pavement widening in Texas typically involves adding lane width, a narrow shoulder, or both to increase the travel way in each direction of a narrow FM and RM road by 1 to 9 ft (0.3 to 2.7 m). The main reasons for roadway widening are usually to do any or all of the following: improve safety, increase structural capacity, and enhance pavement performance. The goal of this study was to investigate the safety effects of narrow pavement widening projects for rural two-lane FM and RM roads in Texas. A before–after comparison study was conducted with the empirical Bayes method to evaluate how wider lanes and shoulders affect crash occurrence, by type and severity. Of the 22 studied projects, analysis showed a 31.5% reduction in total crashes, a 35.7% reduction in run-off-the-road crashes, and a 55.4% reduction in head-on crashes after narrow widening projects were carried out. The projects were also effective in reducing fatal crashes and injuries by about 29.5%. These findings suggest that pavement widening is an effective safety countermeasure on narrow two-lane FM and RM roads in rural areas.